Comparing beam trawl sampling and eDNA metabarcoding for assessing fish diversity in turbid tropical seagrass habitats - Darcy E. Philpott; Joseph D. DiBattista; Michael A. Rasheed; Laura A. Missen; Robert G. Coles; Cecilia Villacorta-Rath; Paul H. York (Estuarine, Coastal and Shelf Science, 2026)

Increasing body size unlocks gelatinous planktivory in a key coral reef fish species - James Gahan; David R. Bellwood; Renato A. Morais; Leo Nankervis; Isabelle Ng; Alexandre C. Siqueira; Cecilia Villacorta-Rath; Sterling B. Tebbett (Coral Reefs, 2026)
Coral reefs depend on the assimilation of off-reef nutrients, particularly from zooplankton, to fuel on-reef productivity. Planktivorous reef fishes thus play a critical role in sustaining a key ecosystem function as the major consumers of plankton. The importance of gelatinous zooplankton to the nutritional ecology of larger-bodied planktivorous fishes is becoming increasingly apparent. Yet, the extent to which feeding on gelatinous plankton within these taxa is a product of ontogeny has not yet been addressed. It has been hypothesised that Caesio cuning , a key planktivorous species that contributes substantially to reef fish biomass on Australia’s Great Barrier Reef, undergoes an ontogenetic diet shift from predominantly non-gelatinous prey as juveniles to a diet composed mainly of gelatinous zooplankton as adults. We examine high-taxonomic resolution DNA metabarcoding of gut contents, with morphometric analyses, to investigate whether changing body size and habitat are linked with a purported dietary transition in C. cuning . We reveal clear evidence of a shift towards increased feeding on gelatinous plankton with increasing body size in C. cuning . Across the sampled habitats, small- and large-sized individuals occupied distinct dietary spaces. The increase in size and ontogenetic dietary shift in C. cuning was also correlated with a transition towards morphological traits associated with feeding and movement in the water column. These results emphasise the importance of gelatinous zooplankton in shaping the distribution, feeding ecology, and productivity of C. cuning on coral reefs and underscore the close connection between large body size and exploitation of gelatinous plankton by reef fishes.

From nets to barcodes: Selecting suitable methods for assessing fish and prawn assemblages in seagrass meadows - Darcy E. Philpott; Cecilia Villacorta-Rath; Joseph D. DiBattista; Michael A. Rasheed; Nathan J. Waltham; Timothy M. Smith; Paul H. York (Marine Environmental Research, 2025)

New Australian frontier in freshwater fish invasion via Torres Strait Islands - Nathan J. Waltham; Natale Snape; Cecilia Villacorta-Rath; Damien Burrows (Biodiversity and Conservation, 2023)
All continents, excluding Antarctica and the Artic, have been affected by incursion from alien freshwater fish species. Australia has not been spared. Four hundred and fifty species have now been declared on the ornamental importation list, making management a real challenge. With approximately 25 non-native species documented, Papua New Guinea (PNG) has likely some problems with invasive freshwater fish. Many of these species have been intentionally introduced to increase access to food as a protein source for remote communities or have spread naturally from western parts of Java and Indonesia, and now constitute a large biomass on some floodplain areas in PNG. The Torres Strait is located between PNG and northern Queensland and was previously a land bridge, though now under higher sea levels the region exists as a series of approximately 300 islands. The threat of further range extension of freshwater fish from PNG into northern Queensland via the Torres Strait Islands is significant, with two invasive fish species already recorded on northern islands of the Torres Strait (climbing perch, Anabas testudineus which has been continually recorded for the past decade; and recently the GIFT tilapia, Oreochromis niloticus ). Here we present a case to control further spread of invasive freshwater fish species towards Australia, using a Land and Sea Ranger program, where Rangers are trained to be confident in the identification of pest fish species and to implement strategies to protect their borders from potential future incursions. The success of this program relies on Rangers to continue partaking in surveillance monitoring of coastal waters, checking and controlling for any new invasive species moving from PNG into Australian waters. We outline the biosecurity obligation under Article 14 of the Treaty between the two nations, which identifies the importance of conservation and protection of coastal floodplains from invasive species, and the spread between both nations.

Telomere dynamics in the Pacific crown-of-thorns seastar (Acanthaster cf. solaris): effect of age, diet, and tissue type - Sarah Lok Ting Kwong; Cecilia Villacorta-Rath; Morgan Pratchett; Sven Uthicke (Coral Reefs, 2023)
Population irruptions of crown-of-thorns seastar (CoTS, Acanthaster spp.) represent a perennial threat to Indo-Pacific coral reefs. Age determination of CoTS is challenging, thereby hindering understanding and management of this nuisance species. Telomeres, which are protective DNA structure found at the ends of eukaryotic chromosomes that shorten at each cell division, have been used to estimate age in wild animals. To investigate the use of telomeres in CoTS, we optimized a quantitative PCR protocol to measure relative telomere length (rTL) in CoTS for the first time. Comparing rTL among four age groups (4, 7, 16, > 24 months post-settlement), we found that adult CoTS generally exhibit shorter rTL than juveniles, which is the first evidence of age-related telomere attrition in CoTS. However, there was large within-age class variation, and no significant relationships were found between adult CoTS rTL and potential age-indicating external features. Furthermore, we found accelerated telomere attrition under sub-optimal diet, where individuals that were fed crustose coralline algae for 16 months exhibited shorter rTL than their counterparts fed on coral. A positive correlation was found between rTL of tube feet and pyloric caeca, suggesting synchronization of telomere dynamics across somatic tissues in CoTS. Overall, our results suggest that rTL could be used to classify CoTS into broad age groups, though individual variation constrains the ability to resolve specific cohorts. The present study contributes to the understanding of telomere dynamics in marine invertebrates, while laying the groundwork for future research into rTL as biomarker for age and potentially stress for CoTS.

Quantifying shedding and degradation rates of environmental DNA (eDNA) from Pacific crown-of-thorns seastar (Acanthaster cf. solaris) - Sarah L. T. Kwong; Cecilia Villacorta-Rath; Jason Doyle; Sven Uthicke (Marine Biology, 2021)

Advancing our understanding of the connectivity, evolution and management of marine lobsters through genetics - Catarina N. S. Silva; Cecilia Villacorta-Rath; Laura N. Woodings; Nicholas P. Murphy; Bridget S. Green; Klaas Hartmann; Caleb Gardner; James J. Bell; Jan M. Strugnell (Reviews in Fish Biology and Fisheries, 2019)

Temporal genetic patterns of diversity and structure evidence chaotic genetic patchiness in a spiny lobster - Cecilia Villacorta‐Rath; Carla A. Souza; Nicholas P. Murphy; Bridget S. Green; Caleb Gardner; Jan M. Strugnell (Molecular Ecology, 2018)
Population structure of many marine organisms is spatially patchy and varies within and between years, a phenomenon defined as chaotic genetic patchiness. This results from the combination of planktonic larval dispersal and environmental stochasticity. Additionally, in species with bi‐partite life, postsettlement selection can magnify these genetic differences. The high fecundity (up to 500,000 eggs annually) and protracted larval duration (12–24 months) and dispersal of the southern rock lobster, Jasus edwardsii , make it a good test species for chaotic genetic patchiness and selection during early benthic life. Here, we used double digest restriction site‐associated DNA sequencing (dd RAD seq) to investigate chaotic genetic patchiness and postsettlement selection in this species. We assessed differences in genetic structure and diversity of recently settled pueruli across four settlement years and between two sites in southeast Australia separated by approximately 1,000 km. Postsettlement selection was investigated by identifying loci under putative positive selection between recently settled pueruli and postpueruli and quantifying differences in the magnitude and strength of the selection at each year and site. Genetic differences within and among sites through time in neutral SNP markers indicated chaotic genetic patchiness. Recently settled puerulus at the southernmost site exhibited lower genetic diversity during years of low puerulus catches, further supporting this hypothesis. Finally, analyses of outlier SNP s detected fluctuations in the magnitude and strength of the markers putatively under positive selection over space and time. One locus under putative positive selection was consistent at both locations during the same years, suggesting the existence of weak postsettlement selection.

Outlier SNPs enable food traceability of the southern rock lobster, Jasus edwardsii - Cecilia Villacorta-Rath; Irina Ilyushkina; Jan M. Strugnell; Bridget S. Green; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; James J. Bell (Marine Biology, 2016)